Type-I hyperbolic metasurfaces for highly-squeezed designer polaritons with negative group velocity - Yang, Yihao (2019)
Hyperbolic polaritons in van der Waals materials and metamaterial heterostructures provide unprecedented control over light-matter interaction at extreme nanoscales. Here we propose a concept of type-I hyperbolic metasurface supporting highly-squeezed magnetic designer polaritons, which act as magnetic analogs of hyperbolic polaritons in the hexagonal boron nitride (h-BN) in the first Reststrahlen band. Compared with the natural h-BN, the size and spacing of the metasurface unit cell can be readily engineered, allowing for manipulating designer polaritons in frequency and space with greater flexibility. Microwave experimental measurements display a cone-like dispersion in momentum space, exhibiting an effective refractive index up to 60 and a group velocity down to c/400. Tailoring the metasurface, we demonstrate an ultra-compact integrated designer polariton circuit including high-transmission 90° sharp bending waveguides and waveguide splitters. The present metasurface could serve as a platform for polaritonics, and find applications in waveguiding, terahertz sensing, subdiffraction focusing/imaging, low-threshold terahertz Cherenkov radiation, and wireless energy transfer.